Social and Political Critique of Islam in Global Scholarship: A Bibliometric Analysis of Scopus-Indexed Publications - Trisno Susilo; Andri Nirwana; Hakimuddin Salim; Kuswardani Dyah Ayu Kusumaningrum (Universitas Muhammadiyah Surakarta, 2024)
The study of Islamic social political critique has developed as an important part of contemporary Islamic discourse that highlights the relationship between religion, power, social structure, and global political dynamics. Although the number of scholarly publications on this theme has shown a significant increase, the existing literature is still fragmented and dominated by external perspectives, particularly from the Western social science tradition. Therefore, systematic mapping is needed to understand the direction of development, epistemological structure, and thematic tendency of the study of socio-political criticism of Islam in the international academic literature. This study aims to map and analyze the development of Islamic social political critique studies through a bibliometric approach using 119 scientific documents indexed in the Scopus database. The data was analyzed quantitatively and visually through mapping of publication distribution by year, journal source, author productivity, institutional affiliation, country of origin, as well as keyword network analysis using VOSviewer software. This approach allows the identification of knowledge production patterns, academic relationships, and temporal and thematic shifts in the focus of studies. The results show that the study of Islamic social political critique has experienced consistent growth, especially since the 2010s, and has developed into an established theme in global academic discourse. The production of knowledge is dominated by Western countries, particularly the United States and the United Kingdom, while the contribution of Muslim countries is still relatively limited. From a thematic perspective, Islamic socio-political critical discourse tends to be concentrated on ideological issues such as Islamophobia, secularism, colonialism, and modernity, with Islam more often positioned as an object of criticism than as an epistemic subject. This study concludes that although the intensity of Islamic social political critique studies is quite high, there are still epistemological inequalities in the perspectives used. Therefore, this study affirms the importance of developing a more dialogical and balanced socio-political critique of Islam, in particular by strengthening an approach rooted in the Islamic intellectual tradition itself. These findings are expected to be a starting point for further research that expands and deepens the contribution of critical Islamic studies in a global context.